This Place, These People - photographs by Nancy Warner ; text by David Stark (Columbia University Press, 2013)
ARO UND the time this book went into production, I read the essay â€œSmall Rooms in Timeâ€ by Ted Kooser, the Nebraskan poet. This sentence struck me: â€œI began to think about the way in which the rooms we inhabit, if only for a time, become unchanging places within us, complete in detail.â€ The photographs in this book tell stories of different farm places. I made them between 2001 and 2008, in and around Cuming County, Nebraska, where my great-grandfather homesteaded and my parents grew up. People in the area helped me find and get access to many of the places. They were amused and curious about why these old broken-down buildings warranted so much of my attention. In 2008 I installed the first large exhibit of the series at the Great Plains Art Museum in Lincoln. The photographs evoked strong emotional reactions from viewers. During this and subsequent exhibit receptions, people approached me with memories and stories triggered by details in the images. My cousin David Stark first learned of the project when Black & White magazine published a selection of the photographs and an interview with me. He was intrigued. During a visit he made to San Francisco in 2010, we got the idea to collaborate on this book. We traveled to Nebraska then, and again in 2011. We sought out and talked to relatives and other people in Cuming County, most of whom had lived in these places. The book began to take shape. Those voices are recorded here just as David heard them. The pairings of the photographs with the text are based not on specific stories, or even their connections with the places shown, but on the voices themselves: the sounds, rhythms, and emotions that seemed to best set off the feeling of each photograph.